Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

6x(8x-3)-2x(24x-6)=36

Sagot :

Tasyha

Answer:

x = -6

Explanation:

[tex]6x(8x - 3) - 2x(24x - 6) = 36[/tex]

➡️ [tex]48 {x}^{2} - 18x - 48 {x}^{2} + 12x = 36[/tex]

➡️ [tex] - 6x = 36[/tex]

➡️ [tex]x = - 6[/tex] ✅